A Sociolinguistic Study of Code - Switching Among Selected Igbo Bilinguals in Anambra State (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study examined the effect of code-switching on the sociolinguistic behavior of selected Igbo speakers of English in Anambra State. Specifically, it explored how code-switching is used to overcome language constraints, reflect social status, discuss topics, express affection, persuade audiences, and show solidarity among Igbo English speakers. Purposive sampling selected 400 participants: 100 final-year Igbo-speaking students from Chukwuemeka Odumegwu Ojukwu University, 100 Igbo traders from Onitsha Main Market, 100 Igbo communicants from Chapel of Redemption at Nnamdi Azikiwe University, and 100 Igbo staff from the Anambra State secretariat. Data were collected through questionnaires and analyzed using descriptive statistics such as mean and standard deviation. Findings indicated that, apart from reflecting social status, code-switching is widely used to overcome language constraints, express affection, persuade audiences, and show solidarity among Igbo English speakers in Anambra. The study suggests that parents should promote the exclusive use of Igbo at home without code-switching, especially among adolescents, as frequent code-switching can reduce their vocabulary development and impair language separation crucial for early vocabulary acquisition. Excessive exposure to code-switching may also hinder young learners’ ability to differentiate languages and affect their language learning mechanisms. Regarding social status, the study recommends restricting code-switching to adult Igbo English speakers to prevent contamination of early language learning. Expressing affection through code-switching should be limited to adults, since frequent switching can disrupt conversations and impair language proficiency. Using code-switching to persuade should be confined to informal settings, as it may cause miscommunication in formal contexts like classrooms. The practice of showing solidarity through code-switching is discouraged, especially among individuals with weaker working memory, as higher exposure correlates with lower language scores. The study advocates discouraging code-switching among adolescent Igbo English speakers to promote better language development and proficiency.